Sensitivity of Mycobacterium tuberculosis to antituberculosis drugs - Ning Rintiswati, Ning Rintiswati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: The tuberculosis control efforts have been alarmed by trend of the widespread emergence of multidrugs resistant Mycobacterium tuberculosis. To anticipate the _problem it is very important to provide clinicians with data on drugs susceptibility of M. tuberculosis periodically.Objectives: This study reviewed the pattern of susceptibility of M. tuberculosis to various antituberculosis drugs, for monitoring of antituberculosis drugs resistant strains of M. tuberculosis, especially in Yogyakarta. Method: Eighty four isolates of M. tuberculosis - collection of the Laboratory of Microbiology Faculty of Medicine Gadjah Mada University - were evaluated for their susceptibility to various drugs, both the first line drugs (INH, streptomycin, rifampicin, and ethambutol), and the second line drugs (kanamycin). Suspension of M. tuberculosis at density of approximately Mac Farland no. 1 standard (108cfu/m1) were cultured on drugs containing medium as well as control medium of Midlebrook 7H10 and incubated for 3 weeks. The number of colony on the drugs containing medium and control medium was reported.Result: The results showed that range of resistance of M. tuberculosis to the overall drugs were 16% to 62%. Resistance to INH .was the lowest (16.66%), whereas the resistant isolates to streptomycin, ethambutol, rifampicin and kanamycin were 27.38%, 34.21 %, 62.50% and 45.78% respectively.Conclusion: 88.10% of isolates were resistant to one or more antituberculosis, 3.58% were resistant to all of the drugs, and only 11.90% of the isolates still sensitive to all of the drugs.Key words: Mycobacterium tuberculosis - resistance - antituberculosis